Instruction on rhythmic structure during learning enhances the breaststroke kick efficiency - Ried, Bettina; Rodrigues, Graciele Massoli; Meira Junior, Cassio M. (Revista Brasileira de Educação Física e Esporte, 2018)
Motor learning can be fostered by visual or auditory instruction conveying information on different features of the skill, like spatial and rhythmic characteristics. For swimming skills like the breaststroke kick, manuals predominantly emphasise spatial features, neglecting rhythmic aspects – even though motor learning considers movement rhythm crucial for distinguishing one skill from another. We aimed to analyse the impact of instruction containing or not the adequate rhythmic pattern information, conveyed by visual or auditory stimulus, on learning the breaststroke kick. Fifty university students, assigned to four experimental groups (auditory, visual, with and without rhythmic information), performed 400 acquisition plus 50 retention and 50 transfer trials during which stroke index, rhythmic and spatial pattern indices and instruction request frequency were mapped. Results showed a marginal difference (p= .075) between higher indices in the retention test of participants receiving information about adequate rhythm, as well as a strong correlation between stroke index and rhythm pattern index, but not with spatial pattern index. No difference between auditory and visual groups was found. This result supports earlier research on the impact of rhythmic information on the learning of complex motor skills, and emphasises the role rhythm plays in skill efficiency and consequently in motor learning.